2022
DOI: 10.1097/bot.0000000000002346
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Multimodal Analgesic Protocol on Short-Term and Long-Term Opioid Use After Orthopaedic Trauma

Abstract: Objective: To determine whether the use of a multimodal analgesic protocol reduced short-term and long-term opioid use in patients hospitalized after orthopaedic trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Walker et al found that a multimodal postoperative analgesia protocol, which included the use of either diazepam or methocarbamol, reduced opioid consumption, improved pain control, and resulted in shorter hospital stays following posterior lumbar fusion surgery 33 . A similar study in orthopaedic trauma patients also found that patients assigned to a multimodal analgesia protocol, which included methocarbamol, had less opioid use postoperatively 34 . To our knowledge, there are currently no studies that have directly evaluated muscle relaxants in the postoperative period following spine surgery or orthopaedic surgery in general.…”
Section: Gaba(a) Subunitmentioning
confidence: 75%
“…Walker et al found that a multimodal postoperative analgesia protocol, which included the use of either diazepam or methocarbamol, reduced opioid consumption, improved pain control, and resulted in shorter hospital stays following posterior lumbar fusion surgery 33 . A similar study in orthopaedic trauma patients also found that patients assigned to a multimodal analgesia protocol, which included methocarbamol, had less opioid use postoperatively 34 . To our knowledge, there are currently no studies that have directly evaluated muscle relaxants in the postoperative period following spine surgery or orthopaedic surgery in general.…”
Section: Gaba(a) Subunitmentioning
confidence: 75%
“…However, increased inpatient opioid use among orthopaedic patients is associated with greater pain, less satisfaction with pain control, and continued chronic opioid use. 10,[39][40][41][42] Given the significant variability that exists in opiateprescribing practices after orthopaedic injury, the lack of universal opiate-prescribing recommendations, and the rising rates of opioid-related deaths as seen in the current opioid epidemic, 43,44 changes in pain management after musculoskeletal injury are necessary, especially in polytrauma patients who may be at increased risk of developing chronic pain and opioid use. 45,46 The lower extremity assessment project study showed that inadequate pain control in the early recovery period after high-energy lower extremity trauma was the largest predictor of long-term chronic pain 7 years postinjury.…”
Section: Discussionmentioning
confidence: 99%
“…MMA is the current recommendation of the Orthopaedic Trauma Association Musculoskeletal Pain Task Force because it is associated with reductions in both short-term and long-term opioid use after orthopaedic trauma. [9][10][11] Despite a recent push for MMA, orthopaedic surgeons may be hesitant to use NSAIDs in fracture patients because of concern for bone healing. However, withholding NSAIDs may also cause harm by increasing narcotic requirements in patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation